2019
DOI: 10.1051/0004-6361/201833713
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of planetary migration on the minor bodies of the early solar system

Abstract: Pebble accretion is an efficient mechanism that is able to build up the core of the giant planets within the lifetime of the protoplanetary disc gas-phase. The core grows via this process until the protoplanet reaches its pebble isolation mass and starts to accrete gas. During the growth, the protoplanet undergoes a rapid, large-scale, inward migration due to the interactions with the gaseous protoplanetary disc. In this work, we have investigated how this early migration would have affected the minor body pop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 99 publications
(145 reference statements)
16
82
0
Order By: Relevance
“…This favors a scenario where the core alone formed at large distances and then migrated inwards. Recent work by Pirani et al (2019) also places Jupiter's core formation in the outer solar system, based on Trojan data, while most of the gas envelope is accreted closer to 5 au, consistent with our fiducial model. The next issue is whether nitrogen and other elements accumulated during core formation would remain trapped in the core, or become well-mixed throughout Jupiter's interior after the planet's gas envelope was captured.…”
Section: Core Formation and Mixingsupporting
confidence: 88%
“…This favors a scenario where the core alone formed at large distances and then migrated inwards. Recent work by Pirani et al (2019) also places Jupiter's core formation in the outer solar system, based on Trojan data, while most of the gas envelope is accreted closer to 5 au, consistent with our fiducial model. The next issue is whether nitrogen and other elements accumulated during core formation would remain trapped in the core, or become well-mixed throughout Jupiter's interior after the planet's gas envelope was captured.…”
Section: Core Formation and Mixingsupporting
confidence: 88%
“…The mass growth of Jupiter then shrinks these orbits into tadpole orbits, originating the asymmetry. Despite this good agreement with observations, the simulations of Pirani et al (2019) showed a final mass of the Trojans that is 3-4 orders of magnitude higher than the current one and an inclination distribution that is much flatter than the current one.…”
Section: Introductionmentioning
confidence: 50%
“…Moreover, the late instability of the giant planets has not been simulated in this paper, since the mechanism, time and time-scales of this event are still uncertain. A good fraction of the Trojan's mass is probably lost in this event as shown by Pirani et al (2019) who estimated that only roughly 20% of the Jupiter Trojans survive if the giant planet jumps suddenly from 5.4 to 5.2 au. We conclude that a pre-stirred planetesimal disc is the most likely scenario for the Trojans' capture, since this can explain simultaneously the high inclinations, the low total mass and the asymmetry ratio of the Jupiter Trojans.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations